2017
DOI: 10.1177/0269216316686277
|View full text |Cite
|
Sign up to set email alerts
|

Costs of formal and informal care in the last year of life for patients in receipt of specialist palliative care

Abstract: Costs in the last year of life for patients in receipt of specialist palliative care are considerable. Where inpatient hospice care is available, there are potential savings in hospital costs to offset specialist palliative care inpatient costs. Informal care accounts for a high proportion of costs during the last year of life in each area, underlining the important role of informal caregivers in palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 25 publications
(35 reference statements)
0
50
1
3
Order By: Relevance
“…They use routine administrative data on macrolevel supply, but do not capture the needs and experiences of families, or determinants of outcomes [8,9]. They also do not measure unpaid family supports near end of life, which may be of a similar magnitude to formal utilisation [10][11][12][13]. Rankings must be interpreted carefully as high capacity relative to other health care systems does not necessarily correspond to adequate and equitable supply within that country.…”
Section: Introductionmentioning
confidence: 99%
“…They use routine administrative data on macrolevel supply, but do not capture the needs and experiences of families, or determinants of outcomes [8,9]. They also do not measure unpaid family supports near end of life, which may be of a similar magnitude to formal utilisation [10][11][12][13]. Rankings must be interpreted carefully as high capacity relative to other health care systems does not necessarily correspond to adequate and equitable supply within that country.…”
Section: Introductionmentioning
confidence: 99%
“…International research has produced similar findings, for example, Chai et al report that 76.7% of the full economic cost of palliative care in Canada is borne by patients’ caregivers in the form of unpaid care 8. More recently, Brick et al  reported that informal care costs account for more than 22% of costs during the last year of life in Ireland 31. Informal care costs are rarely included in economic evaluations in palliative care13 so it is perhaps unsurprising that these costs are largely absent from the studies in this review.…”
Section: Discussionmentioning
confidence: 82%
“…In Georghiou et al's 23 study, informal care costs were not included. 10 According to our previous findings, 24,25 the proportion of informal care increases as the disease progresses from local to metastatic cancer and to palliative state. In this study, the mean weekly duration of informal care received was 11 h as compared to 15 h in Round et al's study.…”
Section: What This Study Addsmentioning
confidence: 85%
“…In our study, the total cost of the palliative care period per patient (€21,966) was relatively higher than previously reported. In a recent systematic review by Round et al, 16 in which the cost of care was estimated for people with cancer at the end of life in England and Wales, the total costs of end-of-life care were €11,202 and in The Nuffield Trust research report by Georghiou et al, 23 10 HCC covered three-quarters of the total costs. Productivity costs were not estimated.…”
Section: What This Study Addsmentioning
confidence: 99%